Route selection of distribution network phase to earth fault and positioner - YU NA; CHENG YAN; CHEN BAICHAO; YUAN JIAXIN; FEI WENLI (2017)
The utility model relates to an electric power system earth fault detection technique, concretely relates to route selection of distribution network phase to earth fault and positioner, including transformer substation's generating line, substation transformer and joining in marriage power grid electric transmission line, its characterized in that still includes every traditional zero sequence current transformer of feeder leading -out terminal installation at transformer substation's generating line, installs the zero sequence current carrier signal source at every regional segmentation node of each transmission line of distribution network, and the installation arc suppressing coil is located at substation transformer to installation zero sequence current carrier signal receiver on transformer substation's generating line, tradition zero sequence current transformer gathers every and joins in marriage power grid electric transmission line head end zero sequence current signal for phase to earth fault's rout